Scenery of Staphylococcus implant infections in orthopedics. (November 2011) - Montanaro, Lucio; Speziale, Pietro; Campoccia, Davide; Ravaioli, Stefano; Cangini, Ilaria; Pietrocola, Giampiero; Giannini, Sandro; Arciola, Carla Renata
Infection is still the major complication of orthopedic implants and projections based on the actual trend indicate that total hip and knee arthroplasties and their consequent infection burden are destined to greatly increase. Staphylococcus aureus and Staphylococcus epidermidis are the leading etiologic agents of orthopedic implant infection. Here we report on epidemiology of implant-related Staphylococcus infections in orthopedics, also referring to our experience, and focus on the crucial role of bacterial adhesins and on their ability to direct the pathogenesis process. Bacteria initiate implant infection by adhering to biomaterials. In the early steps of infection, adhesins mediate the specific interaction between microbial cells and the extracellular matrix proteins filming biomaterial surface. Then adhesin-mediated anchorage allows bacteria to cling to the biomaterial surface and to produce a biofilm that favors their ability to resist antibiotics. With the aim to prevent implant-related infections, anti-infective and infection-resistant biomaterials are being developed. The research for novel therapeutic strategies is incited by the emergence of antibiotic-resistant bacteria. Vaccines against the adhesins or antisense molecules against virulence genes can open a future in combating implant infections.